Millets in Indian perspective: Importance, processing and value addition – A review - Sindhu, Marimuthu; Geetha, Padmanaban; Sashidevi, G; Thirupathi, V; Karthikeyan, S; Preetha, P (Plant Science Today, 2024)
Millet is a crop of ancient origins predominantly cultivated in Asian and African nations. This particular crop thrives in arid regions and requires minimal water resources. Notably, millet serves as a dietary staple in certain countries and offers economic opportunities for farmers, contributing to their livelihoods. Following the announcement of the official title of 2023 as the international year of millet, there has been an increased recognition and emphasis placed on millet. This comprehensive assessment aims to provide individuals with a clear understanding of millets by examining aspects such as recent production and consumption in the world, India, and Tamil Nadu, health benefits (cardiac health, gut health, weight management, gluten-free, sugar maintenance, antioxidants rich food), processing techniques (dehulling, milling, soaking, germination/malting, fermentation, flaking, popping, roasting, extrusion and microwave treatment) and the effects of processing on millets. Furthermore, it sheds light on initiatives and schemes from the Indian Government, in addition to the value addition of millets (weaning foods, baked foods, fermented foods, functional foods, beverages, and traditional foods), which can be beneficial for entrepreneurs and to improve a healthy lifestyle among the population. This review discussed the positive environmental effects of millet cultivation and value addition and the recent market of millet-based food products.